PENGARUH DETERMINAN TERHADAP KEPUTUSAN PEMBELIAN KOPI INSTAN GOOD DAY DI KOTA SURAKARTA - Nindyopintoko Juan L.P; Muhammad Jalari (Jurnal AKTUAL, 2022)
The purpose of this study was to determine the effect of product quality, price, promotion and brand image variables on consumer purchasing decisions which is one of Good Day's coffee products in Surakarta. When making a decision to purchase Good Day coffee products, there are important indicators to influence consumers. The indicators that influence purchasing decisions are product quality, price, promotion and brand image. This study uses primary data. The technique used is purposive sampling, certain criteria in purposive sampling can be done based on sampling. The sampling criteria are: People who buy Good Day Coffee, People who are consuming Good Day Coffee, Gender, men and women, People who live or are domiciled in Surakarta City. The results of the study stated that product quality, price, promotion and brand image had a positive effect on purchasing decisions for Good Day coffee products in Surakarta.